'Everything we do will have an element of fear in it': challenging assumptions of fear for all in outdoor adventurous education. Issue 2 (3rd April 2023) - Reed, Jack; Smith, Heidi
ABSTRACT: Challenge, adventure, and risk in outdoor adventurous education (OAE) have long been recognised as foundational components in the framing of valuable and transformational experiences for participants. Whilst the literature has identified the benefits of these types of learning experiences, what has remained largely absent is an interrogation of the emerging emotional effects surrounding the fear response. This paper presents the examined interrelationships of facilitator perspectives on fear and how fear influences the developmental potential for participants in OAE. Multiple-case study research interviewed four OAE facilitators and observed participants' experiences of fear-related practice through a caving activity. The findings demonstrate a distinct and complex tension between the intentional facilitation of fear and the diverse impact fear can have for participants. Two primary outcomes emerged: the historically situated assumptions of a fear for all approach are challenged, and fear was recognised to isolate and marginalise participants unable to successfully interact with fear.